Leo Brouwer and the appearance of cubanity in Parabola - Mesa Zabala, Luis Yesid (UNIVERSIDAD ANTONIO NARIÑO, 2014)
This article focusses on an analysis as well as some broad conclusions based upon the most remarkable characteristics which contribute the consideration of “Parabola” by the Cuban composer Leo Brouwer as an avant-garde work of music. To serve such a purpose, the argumentative logic displaces from a descriptive exposition of cultural elements which make up the concept of cubanity to systematic constrictions both rational and immanent of the surpassing of the traditional concept of work of art by outstanding historical events in the so called political and artistic metropolis, and also in the peripheral political and artistic thought of Latin America